Promoting Teachers’ Professionalism in Primary School: The Female Principal’s Leadership Style - Etika Wulandari, Jeinin; Waris, Waris; Sugiarti Dwi Gita, Rina (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Leadership style these days is becoming crucial aspect in managing programs in educational setting. The principal is required to carry out effective leadership to promote the success of education. In addition, this leadership style can be a means to promote teacher’s professionalism. Still, there has been the lack of effective leadership leading to unmotivated teachers and the lack of teacher’s professionalism. There has ben previous studies concerning on the principal leadership style in elementary school. However, this study focuses on the female principal’ leadership style to fill the gap. Method: This study is qualitative case study. It aims at exploring the female principal’s leadership style to promote teacher’s professionalism at SD Negeri Tambahrejo 03. The participants of this study are one principal and four teachers at SD Negeri Tambahrejo 03. To collect the data, the researcher uses semi-structured interview. Results: Based on the result of data analysis using semi-structured interview with the participants, it shows positive influence of leadership style to promote teacher’s professionalism. It shows that there are two leadership styles used by the female principal; transformational and situational leadership. In addition, this leadership style is to promote teacher’s professionalism through the following activities; professional development, teachers forum, and curriculum development. In short, leadership style plays a significant role in promoting teacher’s professionalism. In other words, the more effective leadership style used by the principal, the higher teacher’s professionalism.